Indeks Kenyamanan Termal Di Universitas Mataram : Thermal Comfort Index at Mataram University - Gozali, M. Rijalul; Latifah, Sitti; Aji, Irwan Mahakam Lesmono (HUTAN TROPIKA, 2023)
Green Open Space (RTH) is an open area with land use dominated by vegetation. Vegetation is able to provide comfort because it can affect the microclimate.This study aims to determine the thermal comfort index of Mataram University's green open space from microclimate conditions obtained from measurements of temperature, humidity, light intensity and perceptions of the Mataram University academic community. The research method used is descriptive research method with a quantitative approach. Measurements were made at 20 points in 10 zoning by purposive sampling based on the criteria for vegetated areas and open areas. The results showed that the green open space of Mataram University had a significant difference in the level of comfort at 3 (three) times of observation, with the average THI value in the morning 24.7 (comfortable), 28.4 (uncomfortable) in the afternoon and 26.6 in the afternoon (comfortable). While, the perception of the academic community regarding the comfortable conditions felt at green open space of the University of Mataram in the morning and afternoon felt comfortable with the morning being the most comfortable time, while during the daylight they felt uncomfortable. The level of comfort felt by each person is different which is influenced by many factors such as air temperature, wind movement, humidity, solar radiation. The higher humidity and the lower air temperature, then THI value level at the University of Mataram is categorized as comfortable.